Sosialisasi Implementasi Konsep Green Building Pada Rumah Hunian Bagi Siswa SMK di Kota Mataram - M Khairul Zahidi; Hariyadi; Hartana; Ida Ayu Oka Suwati Sideman (Universitas Mataram, 2026)
The knowledge gap in sustainable building design exists in the vocational high school (SMK) education system, where the curriculum still focuses on traditional methods rather than sustainability principles. This initiative addresses the lack of sustainable design knowledge among vocational students in Mataram by teaching the basics of green residential planning, with a focus on passive cooling and the selection of environmentally friendly materials. The program was delivered through face-to-face lectures, followed by evaluation using pre- and post-intervention questionnaires. The activity utilized face-to-face lectures, which were then evaluated using pre- and post-socialization questionnaires. The comparative evaluation results showed a significant increase in understanding; for example, fundamental green building literacy increased from 12.5% ​​to 71.4%, and students' readiness to design energy-efficient residential buildings jumped from 50% to 85.7%.